Pengaruh Sistem Informasi Manajemen dan Kompetensi Terhadap Efektifitas Kerja Pegawai di Dinas Pendidikan Kabupaten Ogan Komering Ilir - Rizki, Arya Prameswara; Hendri, Edduar; Darmawati, Tri (Peneliti.net, 2024)
This study aims to test the hypothesis of the influence of management information systems and competency on work effectiveness. The research model used is quantitative associative. The population of this study is all 50 civil servants (PNS) employed at the Department of Education in Ogan Komering Ilir Regency. The sampling technique used is non-probability sampling with a saturated sample method. Data for this research were collected using primary data through the distribution of questionnaires to respondents and secondary data by collecting relevant documentation and literature studies related to the research. Data analysis techniques used include normality test, heteroscedasticity test, and multicollinearity test. Hypothesis testing used t-test and F-test. The results of the t-test show that the value of management information systems is 5.495 > 2.01174 and competency is 4.224 > 2.01174. Meanwhile, the results of the F-test also show a value of 142.955 > 3.20, indicating that both management information systems and competency significantly influence work effectiveness, both partially and simultaneously. This is further supported by the coefficient of determination, which indicates that 85.3% of the work effectiveness is influenced by the variables studied, while the remaining 14.6% is influenced by other factors.